2023
DOI: 10.3390/metabo13020250
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Lipopolysaccharide-Binding Protein Concentration with Dietary Factors, Gut Microbiota, and Health Status in the Japanese General Adult Population: A Cross-Sectional Study

Abstract: The influx of intestinal bacteria-derived lipopolysaccharide (LPS) into the blood has attracted attention as a cause of diseases. The aim of this study is investigating the associations between the influx of LPS, dietary factors, gut microbiota, and health status in the general adult population. Food/nutrient intake, gut microbiota, health status and plasma LPS-binding protein (LBP; LPS exposure indicator) were measured in 896 residents (58.1% female, mean age 54.7 years) of the rural Iwaki district of Japan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 138 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Probiotics and prebiotics are well known as potential influences on blood LPS levels [ 7 ]. In our previous cross-sectional study, we have found dietary factors associated with plasma LPS-binding protein concentrations (LPS exposure indicator): vitamins, carotenoids, lipids, fatty acids, dietary fiber, potassium, alcohol, and several foods (fish, green tea, cruciferous vegetables, and tomato) [ 55 ]. Participants in the current study did not take any medications or dietary supplements during the study period, thus excluding the possibility that they influenced the inter-day variation in plasma LPS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and prebiotics are well known as potential influences on blood LPS levels [ 7 ]. In our previous cross-sectional study, we have found dietary factors associated with plasma LPS-binding protein concentrations (LPS exposure indicator): vitamins, carotenoids, lipids, fatty acids, dietary fiber, potassium, alcohol, and several foods (fish, green tea, cruciferous vegetables, and tomato) [ 55 ]. Participants in the current study did not take any medications or dietary supplements during the study period, thus excluding the possibility that they influenced the inter-day variation in plasma LPS concentrations.…”
Section: Discussionmentioning
confidence: 99%